Pregnancy Characteristics Of Conjoined Twins Born At Dr. Soetomo Hospital Surabaya Period 2010-2019 - Desetyaputra, Dimas Ryan (UNUSA Press, 2021)
Background: Conjoined twins are a rare complication of pregnancy. The prevalence of occurrence is 1 in 200,000 pregnancies. As many as 40% of babies in cases of conjoined pregnancies die at birth and 30% die in the first days of life. Objective: To present the characteristics of a conjoined pregnancy born in Dr. Soetomo Hospital, Surabaya, 2010-2019 period which is a referral hospital in Eastern Indonesia. Methods: This study is a retrospective descriptive study on the case of conjoined twins born in Dr. Soetomo Hospital, Surabaya, in the 2010-2019 period. The data is taken from the electronic medical record of Dr. Soetomo Hospital. Results: In this study, there were 16 cases of conjoined twins who were born in Dr. Soetomo Hospital. Most cases were conjoined twins of Thoracoabdominopagus (12 patients), Parapagus (2 patients), Cephalopagus (1 patient), and Omphalopagus (1 patient). Methods of delivery of conjoined twins were performed with caesarean section (9 cases), and vaginal delivery (7 cases). There were 9 cases of babies who died immediately at birth, and 7 cases of babies who were still alive until a few hours and a few days after birth. The age at diagnosis of conjoined twins was found at gestational age <20 weeks (6 cases), and when gestational age> 20 weeks (10 cases). Conclusion: This case of conjoined twins is a rare case and requires multidisciplinary discussion. Early diagnosis is necessary to terminate the pregnancy as early as possible, in order to reduce the Caesarean Section delivery rate. In Dr. Soetomo Hospital for the period 2010-2019, the most cases of conjoined twins were Thoracoabdominopagus. Keywords: Conjoined twins, Pregnancy